(untitled) (Research, Society and Development, 2020)
The text, Graduates of technical courses in Agriculture: analysis of academic productions, aims to catalog Brazilian academic productions from 2008 to 2020 resulting from research with graduates of agricultural and agricultural education courses. The text was constituted from the cataloging and analysis of the works available in the Brazilian Digital Library of Theses and Dissertations (BDTD). Silvestre (2008), Caú (2017), Vieira (2015) and Matos (2017), among others, contributed to this moment of the research. Methodologically, this research is classified as bibliographic, descriptive and qualitative and is based on the studies of Yin (2016), Gatti (2004), Lüdke and Andre (1996) and Pasqualli, Vieira and Vieira (2015). The results obtained emphasize that the technical course goes far beyond the expectations of the students, and it is the duty of the State to provide the least favored classes with conditions for qualified insertion in the world of work in order to reduce social differences and exclusions.